Silicate positive electrode material and preparation method and application thereof
By doping nickel ions in MgMnSiO4, the problem of low magnesium storage capacity and structural distortion of this material in magnesium ion batteries is solved, and the improvement of material performance and optimization of battery performance is achieved.
Patent Information
- Application Number
- CN202411820319.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The existing MgMnSiO4 materials have low magnesium storage capacity in magnesium ion batteries, and have poor structural distortion and cycling performance caused by manganese ions.
By doping nickel ions in MgMnSiO4 and replacing part of manganese elements, the structure of MgNixMn1-xSiO4 is formed, the grains are refined, the electron conduction performance of the material is optimized, and the Jahn-Teller distortion effect is reduced.
It significantly improves the magnesium storage capacity and conductivity of the material, enhances the stability of the structure, extends the cycle life of the battery, and reduces production costs.
Smart Images

Figure CN119627098A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of magnesium ion battery electrode materials, and in particular to a silicate positive electrode material and a preparation method and application thereof. Background Art
[0002] In today's era, modern science and technology are developing rapidly, battery energy storage systems are widely used in various fields, and the demand for high-performance batteries is rising sharply. Magnesium-ion batteries have emerged with excellent safety and low production costs, and are expected to inject strong vitality into the innovation of energy storage technology and become a key force in promoting the progress of the industry.
[0003] However, the strong polarization effect of magnesium ions constitutes a key obstacle to its development. When magnesium ions come into contact with positive electrode materials, their polarization force will cause the electron cloud of atoms or ions in the positive electrode material to distort. This change first impacts the stability of the crystal structure of the positive electrode material, causing lattice distortion and local collapse, which seriously hinders the embedding and de-embedding process of magnesium ions in the positive electrode material, causing a significant decrease in the ion diffusion rate and a sharp increase in the charge and discharge resistance, which in turn has a serious negative impact on the rate performance of the battery. Secondly, due to structural damage, the number of active sites in the positive electrode material is reduced, resulting in the actual capacity of the battery being far lower than the theoretical value, and during the cycle use, the capacity decay rate is significantly accelerated, which greatly reduces the energy density and cycle performance of the battery. Therefore, exploring positive electrode materials that can effectively resist magnesium ion polarization and have both high energy density and excellent performance has become an extremely urgent task in the current field of magnesium ion battery research.
[0004] Among many cathode materials, olivine silicate materials have attracted much attention due to their stable three-dimensional open skeleton structure, effective resistance to magnesium ion polarization reaction, high ion diffusivity and large theoretical capacity. The multivalent transition metals in their structure can reduce the degree of damage to the host material during the magnesium ion deintercalation process, thereby maintaining stable performance during high-rate and long-cycle charge and discharge, greatly improving the safety and cycle performance of the battery system.
[0005] In the olivine-type silicate material family, MgMnSiO 4 It stands out with its theoretical capacity of over 300 mAh / g. However, in practical applications, it is found that its magnesium storage capacity is relatively low, and this defect has become a major problem in MgMnSiO 4The key obstacles in the application of magnesium-ion batteries make it difficult to apply them on a large scale in actual battery products. Therefore, it is urgent to conduct in-depth research and improve the positive electrode materials of magnesium-ion batteries. Only in this way can we effectively make up for the shortcomings of existing technologies and provide strong support and powerful driving force for the continuous development of magnesium-ion battery technology and the steady advancement of commercialization, so as to meet the growing demand for high-performance battery applications and further expand the application prospects of magnesium-ion batteries in new energy industries and other fields. Summary of the invention
[0006] The present invention is intended to provide a silicate positive electrode material and a preparation method and application thereof to solve the existing MgMnSiO 4 The problem of low magnesium storage capacity of the material.
[0007] To achieve the above object, the present invention adopts the following technical solution: a silicate positive electrode material, whose chemical formula is MgNi x Mn 1-x SiO 4 , where 0 <x≤1。
[0008] The present invention also provides another technical solution, a method for preparing a silicate positive electrode material, comprising the following steps:
[0009] S1: ball-milling and mixing magnesium source, nickel source, manganese source, silicon source and flux in a certain proportion to obtain a Ni-doped precursor;
[0010] S2: drying the Ni-doped precursor prepared in S1;
[0011] S3: Pre-sintering the Ni-doped precursor after drying in S2 under a protective atmosphere, first at 300-400°C, keep warm for 2-3 hours; then raise the temperature to 800-1000°C, continue to keep warm for 6-8 hours, and after cooling to room temperature, wash and dry, finally obtain MgNi x Mn 1-x SiO 4 Ni-doped silicate cathode material.
[0012] Preferably, in S1, the molar ratio of the magnesium source, the nickel source, the manganese source, the silicon source and the flux is 1:x:(1-x):1:5, wherein 0 <x≤1。
[0013] Preferably, in S1, the ball milling speed is 250-350 rpm and the time is 6-12 h.
[0014] Preferably, in S1, the magnesium source is any one of magnesium oxide, magnesium acetate, magnesium carbonate, magnesium hydroxide, and magnesium nitrate; the nickel source is any one of nickelous oxide, nickel nitrate, and nickel acetate; the manganese source is any one of manganese carbonate, manganese acetate, manganese carbonate, manganese oxide, and manganese nitrate; the silicon source is nano-silicon dioxide; and the flux is any one of potassium chloride and sodium chloride.
[0015] Preferably, in S2, the drying temperature is 55-65°C and the drying time is 6-8h.
[0016] Preferably, in S3, the heating rate is 2-3°C / min.
[0017] Preferably, in S3, washing is performed with deionized water.
[0018] Preferably, in S3, the drying temperature is 55-65°C and the drying time is 6-12h.
[0019] The present invention also provides another technical solution, an application of a silicate positive electrode material, and the prepared silicate positive electrode material is applied to a magnesium ion battery.
[0020] Technical concept of the present invention: The technical concept of the present invention is based on in-depth research and innovative thinking on existing magnesium ion battery positive electrode materials, aiming to overcome the limitations of traditional materials and significantly improve battery performance.
[0021] First, in terms of material selection, the existing nickel-containing silicate MgNiSiO 4 In terms of the system, the conventional idea is to simply replace part of the nickel with other elements with similar radius or chemical properties (such as copper or zinc), and then only make minor adjustments and optimizations to the structure. This traditional idea can often only make local and limited performance improvements within the original structural framework, and it is difficult to achieve a fundamental breakthrough and leap in material performance. Instead, after in-depth research and comprehensive analysis, the innovative selection of MgMnSiO 4 As a basic material, we conduct exploratory research on element doping. This choice is not accidental, but is derived from the meticulous and comprehensive consideration of the characteristics of various different system materials. 4 The material itself has a high theoretical capacity of more than 300mAh / g, showing great potential in energy storage. However, in practical applications, its magnesium storage capacity is relatively low. After careful research, the inventors found that the material is very prone to agglomeration, and the grain size will affect the movement of particles and electrons, thereby interfering with the conductive properties of the material. At the same time, as an intercalation material, the capacity of olivine silicate to store magnesium ions depends on the spatial structure position of the material, and MgMnSiO 4The manganese ions in the battery will form an octahedral complex, and due to the difference in length between the two axial bonds and the four equatorial bonds, the Jahn-Teller distortion effect occurs. This not only causes the material to collapse during the process of removing magnesium ions, which has a serious adverse effect on the cycle performance of the positive electrode material, but also greatly reduces the battery's service life and reliability. However, from another perspective, these existing problems provide a broad potential exploration space for achieving a leapfrog improvement in material performance through the use of sophisticated element substitution strategies, and clarify the foundation and direction for subsequent innovative research.
[0022] In terms of element substitution strategy, nickel was determined to replace MgMnSiO 4 This decision is mainly based on the difference in chemical properties and ionic radius between nickel and Mn, hoping to induce a significant change in the crystal structure of the material. From the perspective of structural change, the radius of nickel ions is smaller than that of manganese ions. After doping, the lattice constant will become smaller, thereby producing a grain refinement effect, effectively alleviating the MgMnSiO 4 The agglomeration phenomenon of the material is reduced, thus creating favorable conditions for improving the magnesium storage performance. At the same time, this substitution can change the strength and length of the chemical bonds between different atoms in the material, affect the degree of electron delocalization and conduction mode, and optimize the electronic conduction performance of the material. More importantly, the use of nickel ions to replace a part of the manganese ions can reduce the transverse and longitudinal chemical bond stretching or compression deformation caused by the Jahn-Teller distortion effect generated by manganese ions when the material stores magnesium, effectively alleviate the collapse problem of the material during electrochemical magnesium storage and magnesium removal, enhance the stability of the structure, and ensure that the material can maintain good performance during multiple charge and discharge cycles. In addition, nickel also has a relatively low cost advantage and a good doping effect. While improving the comprehensive performance of the material, it also takes into account economic feasibility, laying the foundation for large-scale application.
[0023] In summary, the present invention, through a unique basic material selection and element substitution strategy, with the help of the significant changes in material structure and its multi-faceted positive effects on performance, constructs a new and significantly advantageous magnesium ion battery positive electrode material technology solution, which is expected to bring substantial impetus and breakthroughs to the development of magnesium ion battery technology.
[0024] Compared with the prior art, the beneficial effects of this solution are:
[0025] Improvement of material performance:
[0026] (1) Grain refinement and agglomeration improvement and magnesium storage capacity enhancement: Based on the significant differences in ionic radius and chemical properties between nickel ions and manganese ions, effective grain refinement of the material was successfully achieved by in-situ doping with nickel to replace part of the manganese element. This process greatly reduces the MgMnSiO 4The material originally had serious agglomeration. The refined grains make the internal structure of the material more uniform and orderly, reducing the internal stress concentration and electron conduction obstruction caused by agglomeration, while providing a smoother diffusion channel for magnesium ions. Due to the improvement of the agglomeration phenomenon and the optimization of the diffusion channel, more magnesium ions can be effectively embedded in the storage sites of the material, thereby significantly improving the magnesium storage capacity of the material and laying a solid foundation for the subsequent performance improvement.
[0027] (2) Coordinated optimization of conductivity improvement and magnesium storage: The synergistic effect of grain refinement and structural optimization significantly improves the conductivity of the material. During the charge and discharge process of magnesium-ion batteries, electrons can be conducted more smoothly within the material, reducing resistance losses. Good conductivity not only improves the charge and discharge efficiency of the battery, especially at high-rate charge and discharge, it can better meet the needs of fast charge and discharge and improve the overall performance of the battery, but also facilitates the rapid embedding and de-embedding of magnesium ions in the material, further promoting the effective use of magnesium storage capacity in the actual charge and discharge process, so that the material can still maintain a high magnesium storage level under high-rate charge and discharge conditions.
[0028] (3) Enhanced structural stability and guaranteed magnesium storage stability: After nickel ions replace part of the manganese ions, the Jahn-Teller distortion effect produced when the material stores magnesium is effectively reduced. During the electrochemical magnesium storage and de-magnesium process, the structural collapse problem of the material is greatly alleviated, and the structural stability is significantly enhanced. The stable structure ensures the stability and continuity of the magnesium ion storage sites, allowing the material to maintain good crystal structure integrity during multiple cycles of charge and discharge, reducing the magnesium storage capacity attenuation caused by structural damage, greatly extending the battery cycle life, improving the reliability and stability of the battery, and ensuring the stable performance of the magnesium storage capacity during long-term cyclic use.
[0029] Preparation process and cost advantages:
[0030] (1) During the sintering process, the heating rate of this technical solution is controlled at 2-3℃ / min. In this way, it can effectively avoid the situation where the sintering time is too long and the production efficiency is greatly reduced due to the slow heating rate. At the same time, it can also avoid a series of problems caused by too fast heating rate, that is, due to the high heating rate, it is very easy to produce a significant temperature lag between the sample and the set program temperature. This temperature lag may cause the sample preparation to fail, or even if the sintering is successful, the internal pore diameter of the obtained sample will increase abnormally, which will have a serious negative impact on the electrochemical properties of the material and interfere with the performance of the magnesium ion battery positive electrode material. The heating rate range determined by this solution can ensure the smooth sintering process and guarantee the high-quality performance of the material.
[0031] (2) Simple preparation process: The solid phase sintering method is used to achieve in-situ doping of elements. This preparation method has the characteristics of simple process, easy operation and control. It does not require complex equipment and harsh reaction conditions, which reduces the technical threshold and production cost in the preparation process, is conducive to large-scale industrial production, and can stably prepare positive electrode materials with high magnesium storage capacity characteristics.
[0032] (3) Low cost: Nickel itself has a relatively low cost, which reduces the production cost of the entire positive electrode material while ensuring the improvement of material performance, especially the improvement of magnesium storage capacity. x Mn 1-x SiO 4 Nickel-doped silicate positive electrode materials have obvious price advantages in market competition and are easier to promote and apply. They provide strong support for the industrial development of magnesium-ion batteries and can achieve large-scale production of magnesium-ion battery positive electrode materials with high magnesium storage capacity at a lower cost.
[0033] In summary, the present invention solves the problem of MgMnSiO 4 The material faces key problems when used as the positive electrode of magnesium-ion batteries, such as severe agglomeration, poor conductivity, structural distortion caused by manganese ions, and poor cycle performance. The magnesium storage capacity of the material is effectively improved through multiple mechanisms, providing a valuable technical solution for the further development and application of magnesium-ion battery technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 (a) is the silicate positive electrode material MgMnSiO prepared in Comparative Example 2 of the present invention. 4 SEM images of
[0035] Figure 1 (b) is the silicate positive electrode material MgMnSiO prepared in Comparative Example 1 of the present invention. 4 SEM images of
[0036] Figure 1 (c) is the silicate positive electrode material MgNi prepared in Example 1 of the present invention 0.1 Mn 0.9 SiO 4 SEM images of
[0037] Figure 1 (d) is the silicate positive electrode material MgNi prepared in Example 2 of the present invention 0.3 Mn 0.7 SiO 4 SEM images of
[0038] Figure 1(e) is the silicate positive electrode material MgNi prepared in Example 3 of the present invention 0.5 Mn 0.5 SiO 4 SEM images of
[0039] Figure 1 (f) is the silicate positive electrode material MgNi prepared in Example 4 of the present invention 0.7 Mn 0.3 SiO 4 SEM images of
[0040] Figure 2 The silicate positive electrode material MgMnSiO prepared in Comparative Example 1 and Comparative Example 2 of the present invention 4 XRD pattern of
[0041] Figure 3 XRD diagrams of the silicate positive electrode materials prepared in Examples 1-4 and Comparative Example 3 of the present invention;
[0042] Figure 4 The present invention adopts 0.5 mol / L Mg(TFSI) prepared in Example 5 2 / MgCl 2 / DME solution as the electrolyte, the cycle performance comparison diagram of the silicate positive electrode materials prepared in Examples 1-4 and Comparative Examples 1-2;
[0043] Figure 5 The present invention adopts 0.5 mol / L Mg(TFSI) prepared in Example 5 2 / MgCl 2 / DME solution as the electrolyte, the first cycle performance comparison chart of the silicate positive electrode materials prepared in Examples 1-4 and Comparative Examples 1-2;
[0044] Figure 6 The specific capacity-voltage diagram of the silicate positive electrode material prepared in Example 1 of the present invention in a commercially available APC electrolyte;
[0045] Figure 7 The silicate positive electrode material prepared in Example 1 of the present invention is prepared in Example 5 with 0.5 mol / L Mg(TFSI) 2 / MgCl 2 Cycling performance diagram at a current density of 0.5C in / DME electrolyte. DETAILED DESCRIPTION
[0046] The following is further described in detail through specific implementation methods:
[0047] Example 1
[0048] A silicate positive electrode material with the chemical formula MgNix Mn 1-x SiO 4 , where 0 < x ≤ 1. In this embodiment, the value of x is 0.1, and its chemical formula is MgNi 0.1 Mn 0.9 SiO 4
[0049] A method for preparing a silicate cathode material, comprising the following steps:
[0050] S1: Weigh a magnesium source, a nickel source, a manganese source, a silicon source and a flux according to a molar ratio of 1:0.1:0.9:1:5, place them in a ball mill for ball milling and mixing, the ball milling speed is 250 - 350 rpm, and the time is 6 - 12 h to obtain a Ni-doped precursor. Among them, the magnesium source is any one of magnesium oxide, magnesium acetate, magnesium carbonate, magnesium hydroxide, magnesium nitrate; the nickel source is any one of nickel oxide, nickel nitrate, nickel acetate; the manganese source is any one of manganese carbonate, manganese acetate, manganese carbonate, manganese oxide, manganese nitrate; the silicon source is nano-silica; the flux is any one of potassium chloride and sodium chloride. In this embodiment, the ball milling speed is 300 rpm, the time is 8 h, the magnesium source is magnesium oxide; the nickel source is nickel oxide; the manganese source is manganese carbonate; the flux is potassium chloride;
[0051] S2: Dry the Ni-doped precursor prepared in S1, the drying temperature is 55 - 65 °C, and the time is 6 - 8 h. In this embodiment, the drying temperature is 60 °C and the time is 6 h. The purpose of drying is to minimize the water content in the product after ball milling and avoid affecting the temperature during the sintering process. Failure to dry may lead to unsuccessful sintering in the next step.
[0052] S3: Place the dried Ni-doped precursor in S2 in a corundum crucible, and perform pre-sintering using a tube furnace under a protective atmosphere. The heating rate is 2 - 3 °C / min. First, keep it at 300 - 400 °C for 2 - 3 h; then raise the temperature to 800 - 1000 °C and continue to keep it for 6 - 8 h. After cooling to room temperature, wash the obtained material with deionized water 3 - 5 times, and dry it at 55 - 65 °C for 6 - 12 h to finally obtain a Ni-doped silicate cathode material with the chemical formula MgNi 0.1 Mn 0.9 SiO 4 . Among them, the protective atmosphere is argon. In this embodiment, place the dried Ni-doped precursor in S2 in a corundum crucible, perform pre-sintering using a tube furnace under an argon atmosphere, the heating rate is 2 °C / min, first keep it at 350 °C for 2 h; then raise the temperature to 900 °C and continue to keep it for 6 h. After cooling to room temperature, wash the obtained material with deionized water 3 times, and dry it at 60 °C for 12 h to finally obtain a Ni-doped silicate cathode material with the chemical formula MgNi0.1 Mn 0.9 SiO 4 Ni-doped silicate cathode material.
[0053] Example 2
[0054] Different from Example 1, a silicate positive electrode material, the value of x is 0.3, and its chemical formula is MgNi 0.3 Mn 0.7 SiO 4 .
[0055] A method for preparing a silicate positive electrode material, comprising weighing magnesium oxide, nickelous oxide, manganese carbonate, nano-silicon dioxide and potassium chloride in a molar ratio of 1:0.3:0.7:1:5 in S1, and finally obtaining a silicate positive electrode material having a chemical formula of MgNi 0.3 Mn 0.7 SiO 4 Ni-doped silicate cathode material.
[0056] Example 3
[0057] Different from Example 1, a silicate positive electrode material, the value of x is 0.5, and its chemical formula is MgNi 0.5 Mn 0.5 SiO 4 .
[0058] A method for preparing a silicate positive electrode material, comprising weighing magnesium oxide, nickelous oxide, manganese carbonate, nano silicon dioxide and potassium chloride in a molar ratio of 1:0.5:0.5:1:5 in S1, and finally obtaining a silicate positive electrode material having a chemical formula of MgNi 0.5 Mn 0.5 SiO 4 Ni-doped silicate cathode material.
[0059] Example 4
[0060] Different from Example 1, a silicate positive electrode material, the value of x is 0.7, and its chemical formula is MgNi 0.7 Mn 0.3 SiO 4 .
[0061] A method for preparing a silicate positive electrode material, comprising weighing magnesium oxide, nickelous oxide, manganese carbonate, nano-silicon dioxide and potassium chloride in a molar ratio of 1:0.7:0.3:1:5 in S1, and finally obtaining a silicate positive electrode material having a chemical formula of MgNi 0.5 Mn 0.5 SiO 4 Ni-doped silicate cathode material.
[0062] Example 5
[0063] A MgNi x Mn 1-x SiO 4 Electrolyte for silicate cathode material, molecular formula is Mg(TFSI) 2 / MgCl 2 / DME, the concentration is 0.5moL / L.
[0064] A MgNi x Mn 1-x SiO 4 The preparation method of the electrolyte for silicate positive electrode material is as follows: first, weigh Mg(TFSI) at a molar ratio of 1:2 2 With MgCl 2 , weigh the MgCl 2 Add an appropriate amount of 1,2-dimethoxyethane (DME), then turn on the magnetic stirrer to stir at a speed of 500-600r / min, continue stirring for 3-15 minutes, and then slowly add Mg(TFSI) 2 , and continued stirring during the addition process. After stirring for 12 hours, Mg(TFSI) was obtained. 2 / MgCl 2 / DME electrolyte, i.e., MCT electrolyte. In this embodiment, weighed MgCl 2 Add an appropriate amount of 1,2-dimethoxyethane (DME), then turn on the magnetic stirrer to stir at a speed of 550r / min. After stirring for 5 minutes, slowly add Mg(TFSI) 2 , and continued stirring during the addition process. After stirring for 12 hours, Mg(TFSI) was obtained. 2 / MgCl 2 / DME electrolyte.
[0065] Example 6
[0066] A magnesium ion battery comprises a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode is a metal magnesium sheet and the positive electrode comprises MgNi x Mn 1-x SiO 4 Silicate cathode materials, conductive agents and binders, MgNi x Mn 1-x SiO 4 The mass ratio of silicate positive electrode material, conductive agent and binder is 7:2:1, MgNi x Mn 1-x SiO 4The silicate positive electrode material was prepared by the preparation method of the present application, the conductive agent was Super P, the binder was PVDF dissolved in N-methylpyrrolidone (NMP) dispersant, and the electrolyte was 0.5 mol / L Mg(TFSI) prepared in Example 5. 2 / MgCl 2 / DME electrolyte, the volume of the electrolyte is 90μL.
[0067] Comparative Example 1
[0068] Different from Example 1, a silicate positive electrode material, whose chemical formula is MgMnSiO 4 .
[0069] A method for preparing a silicate positive electrode material, in S1, magnesium oxide, manganese carbonate, nano silicon dioxide and potassium chloride are weighed in a molar ratio of 1:1:1:5, and the mixture is placed in a ball mill for ball milling at a speed of 300 rpm for 8 hours to obtain a precursor without Ni doping. After S2-S3, in S3, a precursor with a chemical formula of MgMnSiO 4 Silicate cathode material.
[0070] Comparative Example 2
[0071] Different from Comparative Example 1, a method for preparing a silicate positive electrode material is as follows: in S3, the dried precursor without Ni doping in S2 is placed in a corundum crucible, and pre-sintered in a tube furnace under an argon atmosphere, with a heating rate of 2°C / min, first at 350°C, and kept warm for 2h; then heated to 800°C, and kept warm for 6h, and after cooling to room temperature, the obtained material is washed 3 times with deionized water, and dried at 60°C for 12h, and finally a material with a chemical formula of MgMnSiO is obtained. 4 Silicate cathode material.
[0072] Comparative Example 3
[0073] Different from Example 1, a silicate positive electrode material, the value of x is 1, and its chemical formula is MgNiSiO 4 .
[0074] A method for preparing a silicate positive electrode material, comprising weighing magnesium oxide, nickelous oxide, nano-silicon dioxide and potassium chloride in a molar ratio of 1:1:1:5 in S1, and finally obtaining a silicate positive electrode material having a chemical formula of MgNiSiO 4 Silicate cathode material.
[0075] Comparative Example 4
[0076] Different from Example 1, a method for preparing a silicate positive electrode material, in S1, magnesium oxide, nickelous oxide, manganese carbonate and nano-silicon dioxide are weighed in a molar ratio of 1:0.1:0.9:1:5, and the mixture is placed in a ball mill for ball milling and mixing. The ball milling speed is 300 rpm and the time is 8 hours to obtain a Ni-doped precursor. After S2-S3, a silicate positive electrode material is obtained in S3, and the prepared silicate positive electrode material is subjected to XRD analysis. It is found that no flux is added when the precursor is sintered, resulting in the inability to sinter MgNi at 900 ° C. 0.1 Mn 0.9 SiO 4 Pure phase.
[0077] The silicate positive electrode materials prepared in Examples 1-4 and Comparative Examples 1-2 were photographed and observed using a scanning electron microscope. The results are as follows: Figure 1 By comparing Comparative Example 1 and Comparative Example 2, it can be found that the MgMnSiO 4 The silicate cathode material shows the characteristics of finer grains and more perfect crystal form. This uniform and fine surface morphology has a positive effect on improving the conductivity of the material; on the contrary, the silicate cathode material synthesized at 800℃ shows more significant agglomeration phenomenon, and the particle size is obviously larger. It can be seen that the sintering condition of 900℃ can effectively improve the conductivity of MgMnSiO 4 Agglomeration phenomenon of silicate cathode materials.
[0078] Figure 1 (c) to Figure 1 (f) shows the silicate cathode material after Ni doping. Since the Ni ion radius is relatively small, after being doped into the material lattice, the lattice constant is reduced, which in turn produces the effect of grain refinement. The difference in material performance is related to the surface micromorphology. The finer the particles and the higher the degree of dispersion, the larger the contact area with the electrolyte during the electrochemical cycle, so that better electrochemical performance can be obtained. When the Ni doping amount is 0.1-0.7, the particles show an obvious dispersion state, which shows that the nickel element plays an effective role in improving the material agglomeration problem. As the Ni doping amount gradually increases, the micromorphology of the material changes regularly, from the initial stick shape, to a mixed form of plate and stick shape at x=0.1, then to a block shape at x=0.3, and then to a more narrow plate shape at x=0.5, until x=0.7, a uniform, fine and long stick structure is basically formed.
[0079] In summary, sintering at 900 °C helps to improve the agglomeration of silicate cathode materials. Ni doping at 0.1-0.7 can improve the agglomeration of materials, and the best effect is achieved at 0.7. At this time, the uniform and fine stick-shaped materials alleviate the agglomeration of MgMnSiO 4 The particles agglomerate and increase the contact area with the electrolyte, thereby improving the magnesium storage performance.
[0080] The silicate positive electrode materials prepared in Comparative Example 1 and Comparative Example 2 were tested by X-ray diffraction spectroscopy. The results are as follows: Figure 2 Silicate cathode material MgMnSiO sintered at 800°C and 900°C 4 The main characteristic peaks of the synthesized silicate cathode material are consistent with those of the standard card (#83-1546), indicating that the main phase of the synthesized silicate cathode material is MgMnSiO 4 .
[0081] The silicate positive electrode materials prepared in Examples 1-4 and Comparative Example 3 were tested by X-ray diffraction spectroscopy. The results are as follows: Figure 3 Five silicate cathode materials MgNi sintered at 900 °C 0.1 Mn 0.9 SiO 4 MgNi 0.3 Mn 0.7 SiO 4 MgNi 0.5 Mn 0.5 SiO 4 MgNi 0.7 Mn 0.3 SiO 4 MgNiSiO 4 The XRD cards of the samples are shown in the figure. The main characteristic peaks of the cards with doping levels of 0.1-0.7 are consistent with those of the standard card (#83-1546), indicating that the Ni-doped silicate cathode material MgMnSiO4 has been successfully synthesized. However, the MgNiSiO 4 It cannot match the standard card, indicating that MgNiSiO cannot be synthesized under the conditions of the present invention. 4 Pure phase.
[0082] The silicate positive electrode materials prepared in Examples 1-4 and Examples 1-2 were used as positive electrode materials for magnesium ion batteries to verify their performance.
[0083] (1) Using commercially available APC electrolyte as the electrolyte, the silicate positive electrode material prepared in Example 1 was assembled into a button cell. The specific assembly steps are as follows:
[0084] First, the silicate positive electrode material prepared in Example 1 is fully mixed and stirred with Super P (as a conductive agent) and PVDF (binder) dissolved in N-methylpyrrolidone (NMP) dispersant in a mass ratio of 7:2:1 until uniform. Subsequently, the uniformly mixed material is coated on the surface of the carbon cloth cut into 12 mm specifications after ultrasonic treatment. Next, the coated positive electrode sheet is placed in a vacuum drying oven and dried at 60°C for 10 hours to remove volatile components such as solvents therein, thereby obtaining a positive electrode sheet that meets the requirements.
[0085] Then, the finished positive electrode sheet was used as the positive electrode of the battery, the metal magnesium sheet was used as the negative electrode, Whatman GF / A glass fiber filter paper was used as the diaphragm, and the commercially available APC electrolyte was used as the electrolyte. The battery was assembled in an argon atmosphere glove box environment with a water pressure of <0.01ppm and oxygen <0.01ppm. The amount of electrolyte used was 90uL. Finally, the assembled button battery was placed on a sealing machine and a pressure of 80MPa was applied for sealing to ensure the sealing and integrity of the battery assembly, so as to facilitate the subsequent testing and evaluation of battery performance.
[0086] Figure 6 This is a specific capacity-voltage diagram of the silicate positive electrode material prepared in Example 1 in a commercially available APC electrolyte. It can be seen from the figure that the silicate positive electrode material prepared in Example 1 is not compatible with the electrolyte, which causes the battery to be easily short-circuited and the battery cannot work normally.
[0087] (2) 0.5 mol / L Mg(TFSI) prepared in Example 5 2 / MgCl 2 / DME solution was used as the electrolyte, and the silicate positive electrode material prepared in Example 1 was assembled into a button cell. The assembly process was the same as that using the commercially available APC electrolyte, and will not be repeated here. The test was carried out at a current density of 0.5C. Figure 7 It can be seen that the 0.5 mol / L Mg(TFSI) prepared in Example 5 2 / MgCl 2 / DME electrolyte causes the battery's specific capacity to continue to increase at a current density of 0.5C. After 500 cycles, it is still in an activated state and the specific capacity cannot be stabilized at a value. Analysis shows that the reason may be that the MCT electrolyte contains more functional groups, and the activation time is very long at a high current density. The solution is to cycle 10 cycles at a low current of 0.05C for activation and then use a high current cycle of 0.5C to successfully stabilize the battery's specific capacity at a platform.
[0088] (3) 0.5 mol / L Mg(TFSI) prepared in Example 5 2 / MgCl2 / DME solution was used as the electrolyte to assemble the silicate cathode material prepared in Example 1 into a button cell. The assembly process was the same as that using the commercially available APC electrolyte, except that the amount of electrolyte used was 60-70uL. After testing, the battery could not be charged and discharged normally.
[0089] (4) 0.5 mol / L Mg(TFSI) prepared in Example 5 2 / MgCl 2 / DME solution was used as the electrolyte, and the silicate positive electrode materials prepared in Examples 1-4 and Comparative Examples 1-2 were respectively assembled into button batteries. The assembly process was the same as that using the commercially available APC electrolyte, and will not be described in detail.
[0090] Figure 4 0.5 mol / L Mg(TFSI) prepared by Example 5 2 / MgCl 2 / DME solution as the electrolyte, the cycle performance comparison diagram of the silicate positive electrode materials prepared in Examples 1-4 and Comparative Examples 1-2; Figure 5 0.5 mol / L Mg(TFSI) prepared by Example 5 2 / MgCl 2 / DME solution as the electrolyte, the first cycle performance comparison chart of the silicate positive electrode materials prepared in Examples 1-4 and Comparative Examples 1-2. Figure 4 and Figure 5 It can be seen that after 10 cycles of activation at a low current of 0.05C and then cycling at a high current of 0.5C, the magnesium storage performance of the material is greatly improved after Ni doping. Among them, the sample with a doping amount of 0.7 has the highest specific capacity, with an initial discharge capacity of 128.06mAh / g. After 150 cycles, the capacity retention rate is 90%, the coulomb efficiency can be stabilized at around 100%, the capacity decay is slow, and the charge and discharge performance is more stable. Compared with the undoped silicate positive electrode material MgMnSiO 4 The first cycle has 63.3mAh g -1 The discharge specific capacity of the two batteries differs by nearly 2 times.
[0091] The performance verification results of the silicate positive electrode materials prepared in Examples 1-4 and Comparative Examples 1-2 are shown in Table 1.
[0092] Table 1
[0093] sample First discharge capacity / mAh / g First coulombic efficiency / % Capacity retention rate / % Example 1 95.8 89.89 88.31 Example 2 77.5 103.81 93.42 Example 3 88.07 105.16 85.12 Example 4 128.06 103.7 90 Comparative Example 1 63.3 144.29 43.99 Comparative Example 2 49.08 171.5 44.0
[0094] It can be seen from the performance verification results of Examples 1 to 4 that the Ni-doped silicate positive electrode material MgMnSiO 4The positive electrode material has excellent first coulombic efficiency, discharge capacity, and good cycle stability. Especially when the doping amount is 0.7, the specific capacity of the magnesium battery can be increased to twice that of the undoped one. However, as the doping amount increases, the energy required for synthesis also increases, resulting in the inability to synthesize MgNiSiO with a doping amount of 1.0 at 900°C. 4 Materials. Nickel ion doping can effectively reduce the adverse effects of silicate positive electrode materials caused by the collapse of the Jahn-Teller distortion effect and the coarse grain agglomeration during use. It is suitable for application in the field of magnesium batteries and has broad development prospects.
[0095] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A silicate positive electrode material, characterized in that: Its chemical formula is MgNi x Mn 1-x SiO4, of which 0 <x≤1。 2. A method for preparing a silicate positive electrode material, characterized in that: The following steps are involved: S1: ball-milling and mixing magnesium source, nickel source, manganese source, silicon source and flux in a certain proportion to obtain a Ni-doped precursor; S2: drying the Ni-doped precursor prepared in S1; S3: Pre-sintering the Ni-doped precursor after drying in S2 under a protective atmosphere, first at 300-400°C, keep warm for 2-3 hours; then raise the temperature to 800-1000°C, continue to keep warm for 6-8 hours, and after cooling to room temperature, wash and dry, finally obtain MgNi x Mn 1-x Ni-doped silicate cathode material of SiO4.
3. The method for preparing a silicate positive electrode material according to claim 2, characterized in that: In S1, the molar ratios of magnesium source, nickel source, manganese source, silicon source and flux are 1:x:(1-x):1:5, where 0 <x≤1。 4. The method for preparing a silicate positive electrode material according to claim 3, characterized in that: In S1, the ball milling speed is 250-350 rpm and the time is 6-12 h.
5. The method for preparing a silicate positive electrode material according to claim 4, characterized in that: In S1, the magnesium source is any one of magnesium oxide, magnesium acetate, magnesium carbonate, magnesium hydroxide, and magnesium nitrate; the nickel source is any one of nickelous oxide, nickel nitrate, and nickel acetate; the manganese source is any one of manganese carbonate, manganese acetate, manganese carbonate, manganese oxide, and manganese nitrate; the silicon source is nano-silicon dioxide; and the flux is any one of potassium chloride and sodium chloride.
6. The method for preparing a silicate positive electrode material according to claim 5, characterized in that: In S2, the drying temperature is 55-65°C and the drying time is 6-8h.
7. The method for preparing a silicate positive electrode material according to claim 6, characterized in that: In S3, the heating rate is 2-3°C / min.
8. The method for preparing a silicate positive electrode material according to claim 7, characterized in that: In S3, washing is performed using deionized water.
9. The method for preparing a silicate positive electrode material according to claim 8, characterized in that: In S3, the drying temperature is 55-65°C and the drying time is 6-12h.
10. An application of a silicate positive electrode material, characterized in that: The silicate positive electrode material prepared according to claims 2-9 is applied to magnesium ion batteries.
Citation Information
Patent Citations
Rechargeable magnesium cell anode material and preparation thereof
CN101439861A
Method for manufacturing lithium silicate compounds
CN102300811A
Positive electrode active material for magnesium secondary battery, and magnesium secondary battery
JP2013069604A
Positive electrode active material for magnesium ion battery and method for producing the same
JP6229008B1
Polyanion active materials and method of forming the same
US20130029227A1
Cited By
High-performance Mo6S8 material as well as preparation method and application thereof
CN120383336A